EFFECT OF SOME ANTIBIOTICS ON GROWTH OF PROBIOTIC LACTIC ACID BACTERIA - GH. M. Hassan (Mesopotamia Journal of Agriculture)
The effect of different antibiotics on local and imported bacteria Bifidobacterium sp., Lactobacillus acidophilus, L. plantarum, L. bulgaricus , Streptococcus thermophilus, L. Casie has been studied by using Disk assay . All bacteria were found to be sensitive to tetracycline at the concentrations 0.1, 0.2 ppm. The inhibition zone ranged from 12-34 mm . All bacteria except L. acidophilus were inhibited by ampicilline . All bacteria except L. bulgaricus and L. plantarum were found to be sensitive to streptomycine at the concentrations 0.2, 0.4 ppm . The inhibition zones were 13 and 15 mm, respectively, at concentration of 0.4 ppm . Local and imported L. acidophilus were found to be more sensitive to erythromycine . None of the bacteria were affected by cephalexine and chloramphenicol at the concentrations used . All bacteria showed sensitivity toward ampicilline at concentration of 0.2ppm except Strep. thermophilus, L. bulgaricus and L. plantarum which were sensitive to this antibiotic at the concentration of 0.1ppm . All bacteria except L. bulgaricus, local and imported L. acidophilus showed sensitivity to neomycine at the concentrations 0.150 and 0.300 ppm . In conclusion bacteria differed in antibiotics resistance and this must be taken into consideration when using these bacteria as starters in dairy products processed from milk containing residues of antibiotics with inhibiting concentrations to their growth.